Dialogism and monologism : a study of modernity and postcolonialism in Jean Marie Gustave Clézio's Oeuvre. - Kwa, Brennan Yiew Khoon. (2013)
This study of Jean Marie Gustave Le Clézio will investigate the monological aspects of modernity and colonialism as depicted in his literary novels. This investigation shall be divided into two chapters with the first examining the issue of modernity in The Interrogation and The Flood and the second exploring the theme of colonialism in Desert and Wandering Star.